Tratamento da variação linguística no ensino e aprendizagem do Português - SANTOS, Luciani dos Anjos (2019)
The present work focuses on the importance and learning of the treatment of linguistic variation as an essential object of teaching the Portuguese Language. The research sought to deal with the problematization of the possible difficulties that teachers face when applying this language teaching in the classroom, the study was done in two classes of the 7th grade of Basic School of two schools in the municipality of Barcarena / Pará, one of the public network EMEF Mayor Wandick Gutierrez, located in an area with some rural traces and the private network IEPAM Institute of Permanent Education of the Amazon located n an urban area. The study we opted for bibliographical research and field in a quanti-qualitative approach. The instruments were questionnaires containing semi-structured questions, applied to the teachers of the schools in a sample of 1 questionnaire per teacher. Thus, in possession of the information collected it was observed that teachers still have many dificulties in making use of studies of linguistic variation. These teachers are still using traditional and decontextualized techniques and methods. Thus it is understood that it is of the utmost importance that the teacher, from his / her formation, appropriate the knowledge necessary for the development of his / her practice.